Clinical and angiography factors influencing long-term coronary stenting results - S. O. Sokolova; V. P. Mazaev; I. G. Shiman; Yu. M. Popov; S. V. Ryazanova; G. V. Kuznetsova (Кардиоваскулярная терапия и профилактика, 2005)
Aim. To study long-term results of coronary artery (CA) stenting, according to baseline clinical and coronaroangiography (CAG) data. Material and methods. The study included 66 males who underwent coronary stent implantation. One to three years later, all participants were retrospectively divided into several groups. Patients without coronary events (CE) comprised CE- Group (n=44), patients with CE – CE+ Group (n=22). Second CAG was performed in 49 patients with 56 stent-implanted CA. CAG signs of restenosis were not found in 35 stenting cases (Restenosis- Group), being registered in 21 stenting cases (Restenosis+ Group). Stepwise multiple regression was used for analyzing the results obtained. Results. After stent implantation, CE risk was affected by smoking status, number of hemodynamically significant stenoses, low diameter of stented CA, balloon inflation time, and minimal effective intervention (MEI) level. Restenosis risk was linked to unstable angina presence, serum triglycerides level, stenosis type, MEI, and low increase in CA diameter after stenting. Conclusion. In selecting treatment tactics for coronary heart disease patients, and assessing the risk of adverse outcomes after CA stenting, a complex of factors affecting CE and restenosis rates should be taken into account, as well as minimally traumatic technique of coronary stenting should be used.